Nutrient Supply Effects on the Fruit Quality of Apple (Malus domestica Borkh.) - Racskó, József; Drén, Gábor; Thurzó, Sándor (Acta Agraria Debreceniensis, 2005)
The aim of our two year study is to research the effect of nutrient supply on apple fruit quality, and to explore the relationships between selected fruit quality parameters.Observations were made in Kálmánháza (in the eastern part of Hungary), on a commercial apple orchard. In this experiment, we studied the nutrient supply reaction of four apple cultivars (Golden Delicious, Granny Smith, Idared and Jonathan Csány) under different N and NPK doses. The following fruit quality parameters were studied: fruit diameter, fruit height, fruit weight, flesh firmness, colour-coverage and we studied the density of foliage.The research results showed that N fertilization has a great effect on fruit quality. This is shown in the cases of increase of fruit size (fruit diameter, fruit height, fruit weight). The increase is proportional with the N doses, accordingly the highest positive difference was observed by using 100 kg/ha N doses. It is important to note that moderate N doses (75 kg/ha) plus P and K additions also had positive effects. There approached the values of 100 kg/ha N, and even exceeded its values in the cultivar Golden Reinders. The increased N doses enlarged the standard deviation, on the other hand, this parameter was low in the cases of balanced NPK fertilization. The nutrient supply increased the vegetative area (density of foliage) in addition to the generative parts, in particular only N fertilizer. However the denser foliage hindered the growth of fruit weight and colour-coverage, and also decreased the fruit quality and the flesh firmness of cultivars, which have a negative effect on storageability.A linear correlation was demonstrated between the fruit weight and colour-coverage, or between fruit weight and flesh firmness. The character of their relationship was similar, but the direction differed: high fruit weight was with high colour-coverage, but with low flesh firmness.